Giving God the cold shoulder? Naomi’s theological perspective in the book of Ruth - Strollo, Megan Fullerton (Review and expositor, 2025)
Scholarship has tended to prioritize Ruth and Boaz’s faithfulness to family, community, and God as the primary theological message of the book of Ruth. This study focuses on Naomi’s perspective as the central voice in the narrative instead. The book of Ruth begins and ends from Naomi’s perspective; she speaks in the narrative more than any other character, and most importantly, she speaks of God the most. If the narrative is centered around Naomi’s point of view, her perception of God is also most central. Naomi’s theological perspective challenges the received Deuteronomic tradition. In giving God the cold shoulder, Naomi reflects skepticism about God’s presence in difficult periods of life.